In Vitro and In Situ Evaluation of Fermented High Moisture Corn and Ear Corn as Alternative Feedstuffs for Feedlot Calves - Rajaei-Sharifabadi, H.; Villalba, D.; Mora, J.; de la Fuente, G.; Balcells, J.; Seradj, A. R. (Tropical Animal Science Journal, 2025)
High-moisture corn products offer potential advantages in intensive cattle feeding systems by providing high-energy feedstuffs while allowing earlier harvest. This study evaluated the nutritional value and fermentation characteristics of fermented high-moisture grain corn (HMG) and high-moisture ear corn (HME) compared to conventional corn grain (CG) and corn silage (CS) through in vitro and in situ techniques. Six samples from each corn product were collected from commercial farms, pooled, and analyzed in five replicates. Chemical analysis revealed that HME contained higher neutral detergent fiber (19.0% vs. 4.25%) but lower starch (60.95% vs. 66.75%) and crude protein (7.27% vs. 8.32%) compared to HMG (p<0.01). While accumulated gas production was similar among HMG, HME, and CG, all significantly exceeded CS values (p<0.01). HMG demonstrated the highest gas production rate and metabolizable energy content (12.2 MJ/kg), significantly higher than HME (10.1 MJ/kg). In vitro organic matter digestibility was highest in HMG (751.5 g/kg), while HME showed intermediate values (680.2 g/kg). The in situ evaluation revealed higher effective rumen degradability for HMG compared to HME (p<0.01). Ammonia nitrogen concentrations remained above microbial requirements across all treatments, with HMG and HME showing similar patterns. Volatile fatty acid profiles indicated enhanced fiber degradability in high-moisture products compared to CG. In conclusion, fermented high-moisture corn products demonstrated distinct nutritional characteristics compared to conventional corn grain, with HMG showing higher energy content and digestibility values, while HME exhibited increased fiber content. These findings provide quantitative data on the nutritional value of fermented high-moisture corn alternatives for feedlot cattle feeding formulations.